Promoting psychological well-being in doctoral students: a qualitative study adopting a positive psychology perspective. (8th September 2021) - Jackman, Patricia C.; Sisson, Kelly
Abstract : Purpose: Concerns about psychological well-being (PWB) in doctoral students have grown in recent years. The purpose of this study was to explore qualitatively doctoral students' perceptions of factors that promoted their PWB during the doctoral journey. Design/methodology/approach: Nine recent doctoral graduates at an English university participated in the study. Participants recalled their experience and PWB during the doctoral journey via a life grid and semi-structured interview. The life grids were visually inspected to identify high points in PWB whilst the interview data were analysed thematically. Findings: The analysis produced the following seven themes representing factors that participants described during periods of better PWB: accomplishments; intrinsic rewards; self-efficacy; comprehension and understanding; supervisor support; wider support network; and self-care and lifestyle. Originality/value: By adopting a positive psychology approach and exploring qualitatively factors that promoted PWB in doctoral students, this study offers an alternative perspective to research on doctoral student well-being, which has largely adopted a pathological focus. As such, the study demonstrates the utility of approaching research on doctoral students' PWB from a positive psychology perspective. Findings are discussed in relation to the extant literature, and future directions for research are outlined.